Sacred ritual: a study of the West Semitic ritual calendars in Leviticus 23 and the Akkadian text Emar 446 - Babcock, Bryan C. (Bulletin for biblical research supplements, 2014)
"A comparison of the texts regarding ritual in the Old Testament Leviticus 23 and those found in a text from the Syrian site of Emar."-- Provided by the publisher